2011
DOI: 10.1103/physreva.84.023610
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium vortex formation in ultrarapidly rotating two-component Bose-Einstein condensates

Abstract: Equilibrium vortex formation in rotating binary Bose gases with a rotating frequency higher than the harmonic trapping frequency is investigated theoretically. We consider the system being evaporatively cooled to form condensates and a combined numerical scheme is applied to ensure the binary system being in an authentic equilibrium state. To keep the system stable against the large centrifugal force of ultrafast rotation, a quartic trapping potential is added to the existing harmonic part. Using the Thomas-Fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…We have found three different phases: (a) phase coexistence, (b) symmetric phase separation, (c) asymmetric phase separation. As seen in this figure, the phase boundary between phase coexistence and separation of the two components is, to a very good approximation, a straight line given by α 12 = α 2 , which agrees well with the results in [30]. Moreover, it is found that the quartic trap (with strength μ) has only a minimal effect on this boundary condition.…”
Section: Ground State For Nonrotational Casesupporting
confidence: 82%
See 2 more Smart Citations
“…We have found three different phases: (a) phase coexistence, (b) symmetric phase separation, (c) asymmetric phase separation. As seen in this figure, the phase boundary between phase coexistence and separation of the two components is, to a very good approximation, a straight line given by α 12 = α 2 , which agrees well with the results in [30]. Moreover, it is found that the quartic trap (with strength μ) has only a minimal effect on this boundary condition.…”
Section: Ground State For Nonrotational Casesupporting
confidence: 82%
“…For the same reason which leads to a large self-interaction energy for the component 1, component 2 is always surrounded by component 1 in the region (b). However, the area of symmetric phase separation in the parameter space is much smaller than that in [30]. What might be the reason that caused this phenomenon?…”
Section: Ground State For Nonrotational Casementioning
confidence: 86%
See 1 more Smart Citation
“…It is noticeable that, when the all intercomponent and intracomponent couplings are equivalent, with the hamiltonian having an exact SU(2) symmetry, one peculiar structure of the vortex lattice appears, namely, honeycomb and double-core lattices. This has been observed in numerical simulations of the coupled Gross-Pitaevskii (GP) equations [7,10] and Monte-Carlo simulation of similar models [21]. Conversely, the theoretical analysis based on the lowest Landau level approximation has predicted that the vortex stripe, the alternating rows of vortices in each component, is the stable structure [6].…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, two-or multi-component system is of its own merit for fundamental interest especially in regards to the role of the inter-species interaction. For example, two-component BEC systems have been investigated on various properties by a number of groups [12][13][14][15][16][17][18]. Since the first experiment of two coexisting condensates of two different hyperfine states of 87 Rb was realized in 1997 [19] and as the Rydberg dressing technique is mature, it becomes possible to explore a SS state with internal degrees of freedom (SS with a basis or a SS superlattice).…”
mentioning
confidence: 99%